A Positive Versus Negative Interaction Memory Affects Parole Officers’ Implicit Associations Between the Self-Concept and the Group Parolees - Saad, Marina K.; Rivera, Luis M.; Veysey, Bonita M. (Frontiers in Psychology, 2022)
Background: Parole officers are one of many actors in the legal system charged with interpreting and enforcing the law. Officers not only assure that parolees under their supervision comply with the terms of their release, but also monitor and control parolees’ criminal behavior. They conduct their jobs through their understanding of their official mandate and make considered and deliberate choices while executing that mandate. However, their experiences as legal actors may impact their implicit cognitions about parolees. This experiment is the first of its kind to examine implicit (i.e., automatic) associations between the self and parolees among actors of the legal system. Objective: The present study examines the implicit cognitive consequences of the quality of the parole officer-parolee relationship from the perspective of the parole officer; specifically, whether parole officers who are reminded of positive experiences with parolees implicitly associate more with the group parolees than those reminded of a negative experience. In addition, we explore the moderating roles of parole officers’ subjective professional orientation and identification. Method: Eighty-four New Jersey parole officers participated in the study. First, an experimental manipulation of either a past positive or negative experience was administered via a writing task. Participants then completed an Implicit Association Test (IAT) to measure associations between the self-concept of parole officers with parolees who are part of the group criminal, followed by measures of professional orientation and identification. Results: Participants who were reminded of a positive experience with a parolee exhibited stronger associations between self and the group parolee when compared to those who were reminded of a negative experience. Neither professional orientation nor parole officer group identification were related to implicit associations and did not moderate the effect of the past experience reminder on implicit associations. Conclusion and Implications: Implicit cognitions of parole officers may influence their behaviors and interactions with those whom they supervise. Positive reminders affect implicit self-associations with parolees presumably via empathy, which is known to affect the quality of therapeutic and supervision relationships; thus, theoretically, leading to improved outcomes for both officers and parolees.